European National News. Issue 2 (April 2016) - Pantlin, Nick
Abstract: The regular article tracking developments at the national level in key European countries in the area of IT and communications – co-ordinated by Herbert Smith Freehills LLP and contributed to by firms across Europe. This column provides a concise alerting service of important national developments in key European countries. Part of its purpose is to complement the journal's feature articles and briefing notes by keeping readers abreast of what is currently happening "on the ground" at a national level in implementing EU level legislation and international conventions and treaties. Where an item of European National News is of particular significance, CLSR may also cover it in more detail in the current or a subsequent edition.